2010
DOI: 10.2967/jnumed.110.081216
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Factor Detection for Selectively Discriminating Unstable Plaques in an Atherosclerotic Rabbit Model

Abstract: Tissue factor (TF), a transmembrane glycoprotein that acts as an essential cofactor to factor VII/VIIa, initiates the exogenous blood coagulation cascade leading to thrombin generation and subsequent thrombus formation in vivo. TF expression is closely related to plaque vulnerability, and high TF expression is shown in macrophage-rich atheromatous lesions, making TF a potential target for detecting atheromatous lesions in vivo. Thus, we prepared 99m Tc-labeled anti-TF-monoclonal antibody (TF-mAb) IgG as a mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Only a few other studies have focused on TF imaging. Temma et al reported the use of a 99m Tc-labeled anti-TF antibody for ex vivo imaging of macrophage-rich atheromatous lesions in rabbits (22). More recently, Hong et al reported the first use of PET imaging of TF expression in subcutaneous xenograft mouse models using a 64 Cu-labeled anti-TF antibody ( 64 Cu-NOTA-ALT-836) (23).…”
Section: Discussionmentioning
confidence: 99%
“…Only a few other studies have focused on TF imaging. Temma et al reported the use of a 99m Tc-labeled anti-TF antibody for ex vivo imaging of macrophage-rich atheromatous lesions in rabbits (22). More recently, Hong et al reported the first use of PET imaging of TF expression in subcutaneous xenograft mouse models using a 64 Cu-labeled anti-TF antibody ( 64 Cu-NOTA-ALT-836) (23).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, various PET/SPECT imaging probes targeting biomolecules related to the progression of atherosclerosis have been developed [18]. Among them, some probes are developed with based on monoclonal IgG and have been evaluated in animal models such as mouse and rabbit [19,20]. In those studies, xenogeneic antibodies were used, whose nonspecific accumulation in atherosclerotic lesions was not taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…[57][58][59][60][61][62][63][64] Currently, atherosclerotic plaques are diagnosed based on the grade of vascular stenosis measured on angiography. However, vulnerability of plaque cannot be judged on angiography because the vascular lumen volume is not related to plaque stability.…”
Section: 56)mentioning
confidence: 99%